(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2015)
We construct sequences of asymptotically optimal quadrature formulae in the Sobolev classes W^3_p ( 1 ≤ p ≤ ∞) , and W^4_1. Sharp error bounds for these quadrature formulae are given.